Modality in Saami-speaking kindergarten and school children - Johansen Ijäs, Johanna (Septentrio Academic Publishing, 2021)
This article examines modal expressions in Saami-speaking kindergarten andschool children aged 4-8 years. The aim is to explore the ways in which childrenuse language to express different types of modality, and to investigate whetherthere are similarities and/or differences between kindergarten children and schoolchildren with regard to modal expressions. The study is based on transcripts ofconversations between children and adults about stories containing ethical andmoral dilemmas. The conversations lasted a total of ninety minutes. The results show that the children expressed agent-oriented (deontic anddynamic) modality slightly more than propositional (epistemic and evidential)modality. Modality was generally expressed by verbs; the most frequent verbswere the evidential diehtit (‘to know’) and the deontic, dynamic and epistemicalsáhttit ‘may, can’. Most other verbs were deontic, such as fertet ‘must’, galgat ‘tohave to’ and oažžut ‘to be allowed to’. Particles and adverbs, such as the emphaticgal and oainnat ‘you see’, were commonly used to express epistemic and evidentialmodality. In addition, the children used the construction (ii) leat + lohpi ‘[it] is(not) allowed’ and the imperative mode, both of which express deontic modality,and the evidential noun phrase mu mielas ‘in my opinion’. The data from the school children contained slightly more expressions of modality than the data from the kindergarten children, and the school children also had a few more different ways of expressing modality than the kindergarten children. Artihkal guorahallá modalitehta almmuheami 4–8-jahkásaš mánáidgárdemánáid jaskuvlamánáid gielas. Dutkanmateriála vuođđun leat mánáid ja rávisolbmuid ságastallamat muitalusaid birra main leat ehtalaš ja morálalaš čuolmmat. Ságastallamat biste oktiibuot 1,5 diimmu. Bohtosat čájehit ahte mánát almmuhedje sihke daguide (agent-oriented) ja dieđu doallevašvuođa árvvoštallamii (propositional) guoskevaš modalitehta. Modalitehta almmuhuvvui dábálepmosit vearbbaiguin, earenoamážit diehtit-, ...